Annulus Fibrosus Repair. (May 2014) - Li, Zhen; Peroglio, Marianna; Grad, Sibylle; Eglin, David; Alini, Mauro
Intervertebral disc (IVD) herniation is a common origin of disabled spine and low back pain (LBP) which cause enormous health care toll. The annulus fibrosus (AF), which constitutes the outer part of the IVD, plays a key role in the mechanical and biological integrity of the IVD. Closure and repair of ruptured AF in herniated discs is yet an unmet clinical need. As a standard surgical treatment for disc herniation, discectomy leaves the ruptured AF as it is in case of limited discectomy, and even creates further invasion of the ruptured AF in case of subtotal discectomy. Despite high rates of safety and success in relieving pain and improving function, 20 to 25% of discectomy patients continue to experience unsatisfactory results, 1 with recurrent disc herniation as one of the most important factors contributing to the poor outcomes. Larger annular defects increase the rate of reherniation, 2, 3 which indicates that repair of ruptured AF is necessary in case of large disc protrusion. Several groups have tried to close the AF defect with direct suture after discectomy, but they could not draw up consistent conclusions. In a 2-year follow-up study, suture of ruptured AF reduced reherniation risk in patients with predominant leg pain before discectomy but did not significantly affect the reherniation rate in the overall study. 4 Chiang et al assessed an AF suture device in porcine model both ex vivo and in vivo. The suture repaired discs succeeded against repeated compression forces ex vivo and showed lesser degenerative changes compared with unrepaired discs in vivo. 5 However, in another in vivo sheep study, suture of AF incisions did not significantly alter the healing strength of IVD after discectomy. 6 Heuer et al also suggested that suture alone is not enough for long-term reliable AF closure. 7 Our group has established a polyurethane (PU) patch and suture composite for AF defect closure. The composite was assessed in an organ culture system under simulated physiological loading condition. After repetitive dynamic load within a bioreactor, the sutured PU patch successfully maintained a tissue engineering (TE) construct inside AF defect of IVDs without nucleus pulposus (NP) protrusion. 8 This ex vivo model may be used to investigate different cells and/or drug delivery strategies for AF regeneration. As mechanical property of AF tissue is in the end determined by the components and structure of the biological matrix molecules, mechanical repair alone may not be sufficient to restore the function and integrity of AF if biological repair is not considered, especially in long-term outcome. TE approaches aiming for biological and structural repair of AF have been investigated in the last decade. Of several materials reported in the literature, electrospun scaffolds mimicking the fiber orientation and multilayer structure of AF are advantageous in obtaining mechanical properties similar to the native AF tissue. 9 Supporting treatments such as incorporation of growth factor or platelet-rich plasma could enhance AF regeneration. 10 Mesenchymal stem cells (MSCs) have been studied as potential cell sources for AF TE approaches. We have implanted human bone marrow MSCs into AF defect, and cultured the IVDs for 2 weeks under simulated physiologically relevant load conditions. The results indicate that the MSCs implanted into the AF defect are obtaining at least partially the AF cells phenotype, and implantation of MSCs prevents further degeneration of native AF tissue by upregulating anabolic gene expression and downregulating catabolic gene expression. Recent studies have demonstrated the presence of progenitor cells in NP and AF tissues. 11, 12 Because transplantation of MSCs for cell therapy in clinics is still doubted with a lot of open questions, activation of self-repair mechanisms by utilizing endogenous stem/progenitor cells is therefore emerging as an alternative repair strategy. Chemoattractant-mediated cell migration has been considered as promising strategy for regeneration in various tissues. Our group for the first time investigated the chemoattractant-mediated cell migration in IVD. An ex vivo organ culture degeneration model was developed by high frequency dynamic loading and limited nutrition. We identified that degenerated IVDs release CCL5 chemokine. Furthermore, the endogenous CCL5 release from degenerated IVD recruits MSCs into the discs. 13 This endogenous response may be induced or enhanced for AF regenerative therapy. Further research is needed to identify the fate of MSCs recruited, and the effect of recruited MSCs on resident IVD cells. Disclosure of Interest None declared References Asch HL, Lewis PJ, Moreland DB, et al. Prospective multiple outcomes study of outpatient lumbar microdiscectomy: should 75 to 80% success rates be the norm? J Neurosurg 2002;96(1, Suppl)34–44 McGirt MJ, Eustacchio S, Varga P, et al. A prospective cohort study of close interval computed tomography and magnetic resonance imaging after primary lumbar discectomy: factors associated with recurrent disc herniation and disc height loss. Spine 2009;34(19):2044–2051 Carragee EJ, Han MY, Suen PW, Kim D. Clinical outcomes after lumbar discectomy for sciatica: the effects of fragment type and anular competence. J Bone Joint Surg Am 2003;85-A(1):102–108 Bailey A, Araghi A, Blumenthal S, Huffmon GV; Anular Repair Clinical Study Group. Prospective, multicenter, randomized, controlled study of anular repair in lumbar discectomy: two-year follow-up. Spine 2013;38(14):1161–1169 Chiang CJ, Cheng CK, Sun JS, Liao CJ, Wang YH, Tsuang YH. The effect of a new anular repair after discectomy in intervertebral disc degeneration: an experimental study using a porcine spine model. Spine 2011;36(10):761–769 Ahlgren BD, Lui W, Herkowitz HN, Panjabi MM, Guiboux JP. Effect of anular repair on the healing strength of the intervertebral disc: a sheep model. Spine 2000;25(17):2165–2170 Heuer F, Ulrich S, Claes L, Wilke HJ. Biomechanical evaluation of conventional anulus fibrosus closure methods required for nucleus replacement. Laboratory investigation. J Neurosurg Spine 2008;9(3):307–313 Li Z, Pirvu T, Blanquer SBG, et al. Polyurethane membrane for intervertebral disc annulus rupture closure: feasibility under dynamic loading in an organ culture study. Eur Cell Mater 2013;26:43 (abstract) Nerurkar NL, Baker BM, Sen S, Wible EE, Elliott DM, Mauck RL. Nanofibrous biologic laminates replicate the form and function of the annulus fibrosus. Nat Mater 2009;8(12):986–992 Pirvu TN, Schroeder JE, Peroglio M, et al. Platelet-rich plasma induces annulus fibrosus cell proliferation and matrix production. Eur Spine J 2014; January 28 (Epub ahead of print) Sakai D, Nakamura Y, Nakai T, et al. Exhaustion of nucleus pulposus progenitor cells with ageing and degeneration of the intervertebral disc. Nat Commun 2012;3:1264 Huang S, Leung VY, Long D, et al. Coupling of small leucine-rich proteoglycans to hypoxic survival of a progenitor cell-like subpopulation in Rhesus Macaque intervertebral disc. Biomaterials 2013;34(28):6548–6558 Pattappa G, Peroglio M, Sakai D, et al. CCL5/RANTES is a key chemoattractant released by degenerative intervertebral discs in organ culture. Eur Cell Mater 2014;27:124-136, discussion 136